1996
DOI: 10.1002/(sici)1097-0185(199611)246:3<415::aid-ar13>3.3.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Two fibromuscular transverse ligaments related to the levator palpebrae superioris: Whitnall's ligament and an intermuscular transverse ligament

Abstract: Background: This study was performed to reinvestigate the detailed anatomy of the connective tissues related to the levator palpebrae superioris (LPS).Muterials and Methods: One hundred and twenty human orbits were prepared macroscopically or with the help of an operational microscope. Connective tissues related to the LPS were measured, removed, and prepared for histology. Different staining procedures including immunohistochemistry for a-smooth muscle actin were applied to analyze the quality of these tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 1 publication
0
15
0
1
Order By: Relevance
“…Lukas et al demonstrated a high proportion of elastic fibres, 3 whereas Osanai et al found no elastic fibres in the ligament. 11 The ITL, on the other hand, consistently shows a high percentage of elastic fibres, 3,11 similar to other extraocular muscle pulleys. 12 Although Whitnall ligament and the ITL form the LPS muscle pulley, the paucity of elastic fibres in Whitnall ligament 3-5 is unique in comparison with their abundance in other extraocular muscle pulleys.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…Lukas et al demonstrated a high proportion of elastic fibres, 3 whereas Osanai et al found no elastic fibres in the ligament. 11 The ITL, on the other hand, consistently shows a high percentage of elastic fibres, 3,11 similar to other extraocular muscle pulleys. 12 Although Whitnall ligament and the ITL form the LPS muscle pulley, the paucity of elastic fibres in Whitnall ligament 3-5 is unique in comparison with their abundance in other extraocular muscle pulleys.…”
Section: Introductionmentioning
confidence: 97%
“…10 However, the actual amount of elastic fibres in this ligament is controversial. Lukas et al demonstrated a high proportion of elastic fibres, 3 whereas Osanai et al found no elastic fibres in the ligament. 11 The ITL, on the other hand, consistently shows a high percentage of elastic fibres, 3,11 similar to other extraocular muscle pulleys.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations